A study on maintenance system in Selangor / Mazlan Mohmud - Mohmud, Mazlan (Faculty of Architecture, Planning and Surveying, 2007)
The major functions of local authorities can be summarized as this relates to functions of maintenance and improvement of the environment within the area of jurisdiction. This includes obligatory services such as cleansing, collection and disposal of solid wastes, proper drainage and sewage, sewerage system and beautification programmes. Public amenities, this applies to services such as abattoirs, veterinary services, transportation, burial grounds and crematoria Public health and cleansing, this function includes the provision of sanitation and solid waste management system, cleaning drains and roads and the general upkeep of the environment. The research identifies the problems of maintenance system such as maintenance services for the areas:-Inconsistent schedule of rubbish collection, road improper maintenance and damage, Public services such as street lamp face a problem late to repair and drainage full with rubbish. The qualitative study was examining the perceptions of the public about the issue of maintenance system at local authority area (housing scheme). 35 questionnaires were distributed to each case study (Majlis Bandaraya Shah Alam, majlis Perbandaran Klang and Majlis Perbandaran Subang Jaya) and almost the same total of 105 respondents responded.